FORMULATION ANDEVALUATION OF TRANSDERMAL DRUG DELIVERY OF TORASEMIDE - Yadav, Sanjay Kumar; Gupta, Ravikant; Malipatil, S M; Gupta, S K (International Journal of Innovative Research in Medical Science, 2016)
A skin patch uses a special membrane to control the rate at which the liquid drug contained in the reservoir within the patch can pass through the skin and into the bloodstream. The basic components of any transdermal delivery system include the drug(s) dissolved or dispersed in a reservoir or inert polymer matrix; an outer backing film of paper, plastic, or foil; and a pressure-sensitive adhesive that anchors the patch to the skin. The adhesive is covered by a release liner, which needs to be peeled off before applying the patch to the skin. Drugs administered via skin patches include scopolamine, nicotine, estrogen, nitroglycerin, and lidocaine. Non-medicated patch markets include thermal and cold patches, nutrient patches, skin care patches (a category that consists of two major sub-categories-therapeutic and cosmetic), aroma patches, weight loss patches and patches that measure sunlight exposure.